THU0439 Tocilizumab in giant cell arteritis. national multicenter study of 134 patients of clinical practice. (12th June 2018) - Prieto-Peña, D.; Loricera, J.; Martín-V, J.; Calderón-G, M.; Aldasoro, V.; Varela-G, M.; Ibánez-B, R.; Villa, I.; Aurrecoechea, E.; Castañeda, S.; Humbría, A.; Díez, E.; et al.
Abstract : Background: Giant cell arteritis (GCA) can be refractory to corticosteroids 1–3 . Tocilizumab (TCZ) demonstrated to be effective in two short-term clinical trials. Objectives: To assess efficacy of TCZ in refractory GCA or with side effects to corticosteroids in clinical practice. Methods: Multicenter study on 134 patients with GCA in treatment with TCZ due to lack of efficacy and/or unacceptable adverse events of previous therapy. Results: 134 patients (101 w/33 m); mean age of 73.0±8.8 years. Main clinical features at TCZ onset were: PMR (n=73), constitutional syndrome (n=31), headache (n=70), visual (n=28) and jaw (n=14) affection. Besides steroids, 98 patients also received immunosuppressive agents. table 1 shows evolution during follow-up period. After a median follow-up of 12 [3.7–24] months, it was observed a decrease in:a) CRP from 1.7 [0.4–3.2] to 0.1 [0.0–0.3] mg/dL b) ESR from 33 [14.5–61] to 4 2–9 mm/1st hour and c) Prednisone dose from 15 10–30 to 5 [0–7.5] mg/day. Outcome of patients was:a) discontinuation of TCZ (n=15) due to sustained remission, b) dose reduction due to improvement (n=17) or side effects (n=11), c) withdrawal of TCZ because of side effects (n=12) and d) same dose that at onset (n=73). TCZ had to be discontinued due to: infections, haematological and cardiovascular alterations, neoplasms and heptic toxicity among the most frequent. Table 1: Conclusions: TCZ leads to a rapid and maintained improvement in patients with refractory GCA and/or with unacceptable side effects related to corticosteroids. However, the risk of neutropenia and infection should be kept in mind. References: [1] Loricera J, et al. Semin Arthritis Rheum2015;44:717–723. [2] Loricera J, et al. Clin Exp Rheumatol2014;32(3Suppl82):S79–89. [3] Loricera J, et al. Clin Exp Rheumatol2016; 34 (3 Suppl 97):S44–53. Disclosure of Interest: None declared